Implementation of Coordination in the Organization of One-Stop Integrated Services at the Office/Ministry/Religious Affairs/District/Sintang - My*, Joni; Rochmawati, Ida; Juliana, Ari (Universitas Syiah Kuala, 2024)
In an effort to implement better public services, the Sintang Regency Ministry of Religion Office has built and implemented one-stop services through One-Stop Integrated Service programs and activities at the Sintang Regency Ministry of Religion Office. In the implementation of this one-stop integrated service, it appears that all elements of public service as stipulated by the Minister of Religion of the Republic of Indonesia have not been fulfilled, even though in reality public services can be implemented. This needs to be expressed by looking at one of the management functions, namely the coordination carried out in the implementation of PTSP at the Sintang Regency Ministry of Religion Office. The purpose of this research is to find out about the implementation of coordination between units at the Sintang Regency Ministry of Religion Office in implementing PTSP, the obstacles experienced, and the efforts that will be made, through the coordination indicators proposed by Hendry Fayol which include Cooperation, Building Sections that know the needs of other units, the maintenance section which maintains the condition of equipment, the finance section which provides funding and budget requirements, the security section which carries out asset guarding duties, systematically sequenced work, clear orders, and work plans that are always up to date. The research method uses a descriptive qualitative approach, by conducting observations and interviews with relevant sources. From the results of the research, it was found that in order to carry out coordination in PTSP organizers at the Sintang Regency Ministry of Religion Office, it is necessary to form an organization as coordinator of the implementation of activities starting from planning, action to control of activities, so that orders can be clearly implemented, and efforts to re-collect SOPs that have been made.